Cobalt oxide anchored on nitrogen and sulfur dual-doped graphene foam as an effective oxygen electrode catalyst in alkaline media. (September 2016) - Ma, Xiu-Xiu; He, Xing-Quan
Graphical abstract: A novel non-precious catalyst for ORR and OER has been constructed by a solvothermal method, abbreviated as Co3 O4 /NSGF, which performs excellent bifunctional (ORR and OER) catalytic activities, making it a promising candidate to the noble oxygen electrode catalyst. Highlights: Co3 O4 /NSGF composite was constructed via a hydrothermally assisted synergistic method. Co3 O4 single crystal was embedded in graphene foam and exposes the specific (111) plane. The prepared Co3 O4 /NSGF composite exhibited excellent oxygen reduction reaction and oxygen evolution reaction performance in alkaline media. The synergistic effects between cobalt oxide and N, S dual–doped graphene foam attributed a lot to the enhanced ORR and OER activities. Abstract: Developing highly active bifunctional catalysts for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in the oxygen electrocatalysis based energy conversion or storage remains challenges. Herein, an efficient catalyst of cobalt oxide (Co3 O4 ) nanocrystals grown on nitrogen and sulfur co-doped graphene foam (NSGF) is prepared via a hydrothermal method. Scanning electron microscope (SEM) and transmission electron microscopy (TEM) measurements demonstrate Co3 O4 is of regular single crystal morphology in the Co3 O4 /NSGF composite with 1:1 mass ratio of cobalt to graphene foam. For ORR, the hybrid favors a direct 4e − pathway, similar to that of Pt/C, but outperforms Pt/C with a long-term durability. Besides, it achieves a small overpotential of ∼0.48 V vs. SCE at the current density of 10 mA cm −2 and there is only 0.018 V vs. SCE overpotential increasing after 200 cycles for OER testing. The good electrochemical activities of our fabricated bifunctional catalyst are attributed to electrochemical contributions of the loaded Co3 O4 nanocrystals, the integral structure of three-dimensional graphene foam, the heteroatoms doping effects and the synergistic effects between Co3 O4 and NSGF.